Institutional engineering and political accountability in Indonesia, Thailand, and the Philippines - Ziegenhain, Patrick 1969- (Institute of Southeast Asian Studies, 2015)
Based on social science theories, this title analyses the ways institutional engineering concerning different dimensions of political accountability influenced the quality of democracy in Indonesia, Thailand and the Philippines. The book evaluates the degree these institutional reforms resulted in the deepening, stagnation, or regression of these countries respective democratization processes.